2017
DOI: 10.1055/s-0042-122779
|View full text |Cite
|
Sign up to set email alerts
|

Lumen-apposing covered self-expandable metal stents for short benign gastrointestinal strictures: a multicenter study

Abstract: Use of the fully covered self-expandable metal stent (SEMS) for benign luminal gastrointestinal (GI) stricture (BLGS) has been limited by the migration rate. The role of the lumen-apposing metal stent (LAMS) for BLGS is not well defined. We assessed the safety, feasibility, and efficacy of LAMS for the treatment of BLGS. This was an observational, open-label, retrospective, single-arm, multicenter consecutive case series of patients undergoing LAMS placement for BLGS. Technical success was defined as successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(94 citation statements)
references
References 28 publications
(14 reference statements)
4
88
2
Order By: Relevance
“…I N TOTAL, 19 studies and case reports were identified and included in the review [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] (Table 1 and Fig. S1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…I N TOTAL, 19 studies and case reports were identified and included in the review [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] (Table 1 and Fig. S1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…1). To date, 22 patients in the reviewed literature had a LAMS placed for an esophageal stricture [13][14][15][16]. Anastomotic strictures were the most common indication, seen in 17 of the 22 patients.…”
Section: Esophageal Stricturesmentioning
confidence: 99%
“…Yang et al reported 5 patients who underwent LAMS for esophageal anastomotic or esophageal gastric junction strictures [16]. Only 1 patient had an associated adverse event: stent migration.…”
Section: Esophageal Stricturesmentioning
confidence: 99%
“…This characteristic led to its use in the treatment of benign strictures of the digestive tract. Several studies have assessed its usefulness, although with only a few patients and mostly concerning benign strictures of the upper digestive tract; however, some include postsurgical colon strictures [35][36][37][38]. The clinical success rate improves significantly as compared with the traditional covered metal stents, reducing the rate of stent migration and with a lower complication rate.…”
Section: Novel Treatments: Lumen-apposing Metal Stentsmentioning
confidence: 99%
“…Yang et al [36] presented results for 30 patients, with a clinical success rate of 82.6% after a follow-up period of 100 days. The migration rate was 8%, and complications arose in 13.3%…”
Section: Novel Treatments: Lumen-apposing Metal Stentsmentioning
confidence: 99%